Reologi, sifat aging, termal, dan swelling dari campuran EPDM/NR dengan bahan pengisi carbon black N220 - Yuniari, Arum; Nurhajati, Dwi Wahini; Dewi, Indiah Ratna; Setyorini, Ike (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2016)
The blends of EPDM and NR are immiscible in nature and incompatible. Introducing maleic anhydride as a compatibilizer into the blends was expected to produce compatible blends with balanced mechanical properties. The purpose of this research was to determine the effect of EPDM/NR ratio on the rheological, aging, thermal and swelling properties of the blends. The variation of EPDM/NR ratio were 100/0, 80/20, 70/30, 60/40, 50/50, and 40/60 phr. The blends were mixed using two roll mill. The results showed that the addition of NR affects the maximum torque, scorch time, and optimum vulcanization time. In the blends, EPDM plays an important role in improving aging, swelling, thermal properties.